PRELIMINARY STUDY OF THE IMPLEMENTATION OF KANSEI ENGINEERING METHOD FOR THE EARLY SUSTAINABLE DEVELOPMENT PROCESSED WALLET DESIGN BY USING BANANA MIDRIBS - Kartinasari Ayuhikmatin Sekarjati; Muhammad Ragil Suryoputro; Hari Purnomo (Journal of Engineering and Management in Industrial System, 2019)
Efforts to protect the environment were useful to reduce waste of banana tree which can cause global warming from the burning waste of banana tree. One of the effort to reduce waste of banana tree was used the waste as wallet products’ material. In order for wallet products to be able to compete in the market, it was necessary to have the right design to be able to describe the desires of consumers. The purpose of this research was to design a wallet made from waste of banana tree which can fulfill the needs of wallet consumers in the process of sustainable development. Kansei Engineering was used as a method to translate consumer feelings. Validation tests and evaluation were conducted to examine the research hypothesis using a 5% significance level. Consumer desires in the form of Kansei words that were obtained were strong, durable, waterproof, attractive, simple, neat, has a string, smooth, lightweight, environmentally friendly and multifunctional. Among consumers' wishes (Kansei words), consumers wanted the Kansei words to be strong and environmentally friendly which was prioritized in wallet design. The results of this study were obtained midrib of banana tree wallets in accordance with the wishes of the wallet consumers with the criteria of strong, environmentally friendly and multifunctional, moreover attractive because it shows more the original fiber of the midrib`s banana tree.